2023
DOI: 10.1007/s12079-023-00778-3
|View full text |Cite
|
Sign up to set email alerts
|

The advance of CCN3 in fibrosis

Abstract: The extracellular matrix (ECM) is comprised of various extracellular macromolecules, including collagen, enzymes, and glycoproteins, which offer structural and biochemical support to neighboring cells. After tissue injury, extracellular matrix proteins deposit in the damaged tissue to promote tissue healing. However, an imbalance between ECM production and degradation can result in excessive deposition, leading to fibrosis and subsequent organ dysfunction. Acting as a regulatory protein within the extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 81 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…We extended our studies, examining the effects of task and treatment on CCN3 on muscle, another member of the CCN family with anti-fibrotic properties [ 43 , 48 , 49 ]. We first verified the anti-CCN3 antibody with a Western blot loaded with recombinant CCN3 (rCCN3) protein ( Figure 4 A (left)).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We extended our studies, examining the effects of task and treatment on CCN3 on muscle, another member of the CCN family with anti-fibrotic properties [ 43 , 48 , 49 ]. We first verified the anti-CCN3 antibody with a Western blot loaded with recombinant CCN3 (rCCN3) protein ( Figure 4 A (left)).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that CCN family members and β-catenin interact with various MMPs [ 38 , 49 ]. Therefore, we checked for levels of MMP-1, -2, and -9.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations